Economic Structure, the Exchange Rate and Adjustment in the Federal Republic of Germany : A General Equilibrium Approach. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper traces the effects of an appreciation of the deutsche mark with the help of a computable general equilibrium model under alternative structural policy scenarios. In the first scenario, characterized by severe structural rigidities, the contractionary effects of exchange rate appreciation dominate the expansionary effects so that GDP and employment fall and the external surplus declines only little. In the alternative (and polar opposite) case of free movement of goods, services, and factors, the expansionary effects of the appreciation become more prominent as supply and demand respond much more readily to the relative price changes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet